Fatty fried food toxins as triggering stimuli to immune system interplay in global autoimmune diseases: A systematic review - Saba Anwar; Qamar Abbas Syed; Mahnoor Saleh; Muhammad Saad Akram; Ghayyor Sultan; Sahar Khalid; Anum Ishaq; Gholamreza Abdi; Rana Muhammad Aadil (Journal of Agriculture and Food Research)
Globally, the rate of autoimmune diseases has risen to 3–10 % in the general population. Added sugars, fats, and salty ingredients make people crave more fast foods, which contain toxins, the substances produced by plants and animals poisonous to humans that can tear down the gut-brain barrier, which leads to leaky gut and modifies microbiota density, leading to meta-inflammation and incidence of various autoimmune responses through defined pathways. The purpose of the current systematic review was to respond to the following query: Does the rising level of fatty fried food consumption trigger the major autoimmune diseases such as Crohn's disease, ulcerative colitis, rheumatoid arthritis, systemic lupus erythematous, and multiple sclerosis? To find the evidence in support of the research question, the Population Intervention Comparison Outcome Study design (PICOS) criteria were used, following the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Medline/PubMed, Elsevier Science Direct, Wiley Online Library, and Sage Journals databases were used. Following the PRISMA method and applying inclusion and exclusion criteria, studies published between January 2018 and September 2024, were used. The records were extracted and analyzed using a qualitative approach, hence, no statistical analysis was performed. Although the scientific evidence on this topic has not been thoroughly studied, the studies reviewed confirmed the potential role of fast foods in increasing the incidence of autoimmune diseases.